Valproate Reverses Mania-Like Behavior of Clockdelta19 Mouse and Alters Monoamine Neurotransmitters Metabolism in the Hippocampus - Liu S (Dove Medical Press, 2021)
Shasha Liu,1 Jinxue Wei,2,3 Rongjun Ni,2,3 Tianhao Gao,1 Peiyan Ni,2,3 Liansheng Zhao,2,3 Xiyu Duan,2,3 Xiaohong Ma,2,3 Pak C Sham,4,5 Tao Li1– 3,6 1Beijing Institute of Brain Disorders, Laboratory of Brain Disorders, Ministry of Science and Technology, Collaborative Innovation Center for Brain Disorders, Capital Medical University, Beijing, People’s Republic of China; 2Psychiatric Laboratory and Mental Health Center, West China Hospital of Sichuan University, Chengdu, People’s Republic of China; 3Huaxi Brain Research Center, West China Hospital of Sichuan University, Chengdu, People’s Republic of China; 4Department of Psychiatry, The University of Hong Kong, Pokfulam, Hong Kong, People’s Republic of China; 5State Key Laboratory for Cognitive and Brain Sciences, The University of Hong Kong, Pokfulam, Hong Kong, People’s Republic of China; 6Guangdong-Hong Kong-Macao Greater Bay Area Center for Brain Science and Brain-Inspired Intelligence, Guangzhou, People’s Republic of ChinaCorrespondence: Tao LiPsychiatric Laboratory of West China Hospital, Sichuan University, 1 Keyuan Si Road, Chengdu, Sichuan, 610041, People’s Republic of ChinaEmail litaohx@scu.edu.cnBackground: Mice with a deletion at exon 19 of the circadian locomotor output cycles Kaput gene (Clockdelta19) exhibit mania-like behavior and have been one of the most common animal models for bipolar disorder (BD). The predictive validity of the Clockdelta19 was investigated via studies using lithium previously. Determination of effects of other mood stabilizers on Clockdelta19 mouse would be helpful for better understanding of the mechanism underlined.Methods: Wildtype (WT) and Clockdelta19 mice were treated with saline (n = 10 for WT and n=10 for Clockdelta19) or valproate (VPA) (n = 10 for WT and n=10 for Clockdelta19) for 10 days. The hyperactivity, anxiety-like behaviors and depression-like behaviors were tested. The concentration of monoamine neurotransmitters and their metabolites in the hippocampus of saline or VPA treated WT and Clockdelta19 mouse (n = 8 for each) were also determined.Results: VPA can reverse hyperactivity, lower level of anxiety-like and depression-like behaviors of the Clockdelta19 mouse. Clockdelta19 mouse exhibited lower levels of serotonin (5-HT) and dopamine (DA) in right hippocampus compared to WT mouse. Chronic VPA treatment did not affect the levels of 5-HT and DA, but can reduce the level of levodopa (L-DOPA) in the right hippocampus of Clockdelta19 mouse.Conclusion: Our results indicated that chronic VPA treatment can reverse the mania-like behaviors of the Clockdelta19 mouse and further consolidate the validity of the Clockdelta19 mouse as a model of BD. Monoamine neurotransmitters and their metabolites in the hippocampus are partly regulated by mutation of the Clock gene or VPA treatment.Keywords: bipolar disorder, Clockdelta19 mouse, valproate, mania-like behavior, neurotransmitter